Crust and mantle structure beneath the Azores hotspot—evidence from geophysics - O'Neill, C; Sigloch, K (Springer, 2018)
The Azores hotspot marks the triple junction between the North American, Eurasian, and African plates, and is responsible for the ~20 Ma Azores plateau, and ongoing, off-axis volcanism today. The dynamics of the interaction between the Azores hotspot and the slow-spreading North Atlantic ridge has led to short wavelength V-shaped bathymetric and geochemical anomalies along the mid-ocean ridge, suggesting variations in the flow of mantle plume material towards the southwest. The depth extent of the Azores plume is unclear, or indeed whether it constitutes a traditional plume at all. Surface-wave models have suggested that the “plume” is confined to the upper 250–300 km of the mantle, suggesting either a shallow origin to the Azores hotspot, or that the plume is waning. In contrast, recent finite-frequency body-wave tomography has suggested that the Azores conduit may extend to the core-mantle boundary, and that the Azores, Canary, and Cape Verde hotspots may have a common origin under West Africa. Here we assess geophysical constraints on crustal and mantle structure beneath the Azores hotspot. Geochemical constraints and body-wave tomography results argue for a deep origin of the Azores hotspot. Radial anisotropy suggests significant vertical flow in the vicinity of the hotspot, and this is consistent with the geoid and gravity field. Calculations of plume conduit dynamics in simulations of the global mantle flow field suggest that the present conduit tilts towards West Africa, as observed in the body-wave tomography, and support a common origin for the Azores, Canary, and Cape Verde plumes.